Rosa de Santa María - Puig Tarrats, Esteban (Mercurio Peruano, 2017)
The note seeks to elucidate some points regarding Christian holiness in history from the figure of Saint Rose, maintaining a double historical and theological perspective as well as the significance of canonizations and the devotions to the saints in Christianity. Within this double approach, it presents, in a joint vision, the specific features of Saint Rose of Lima’s sanctity.